The demographic divide: population dynamics, race and the rise of mass incarceration in the United States - Campbell, Michael C. (Punishment & society, 2019)
This manuscript examines whether certain fundamental demographic changes in age structures across racial groups might help explain incarceration rates in the United States. We argue that a “demographic divide”—a growing divergence in the age structures of blacks and whites—was an important factor that contributed to the nation’s rising incarceration rates. Where age disparities between blacks and whites were higher ideological conservatism and religious fundamentalism increased, as did incarceration rates. We contend that historical forces shape how groups respond to subsequent social problems and proposed solutions to them and explore how “generational effects” may shape law and policy. Specifically, we suggest that states with older white and younger black populations created fertile conditions for a more punitive brand of politics and penal policy. We analyze decennial state-level data from 1970 to 2010 and examine whether differences in the median ages of blacks and whites contributed to changing incarceration rates within states over time. We situate our findings within the broader scholarship that has engaged the complex links between race, religion, political conservatism, and punishment. Our findings illustrate the importance of accounting for long-term shifts in social structure in understanding more proximate changes in law and policy.